Screening of Tuberculosis Infection through Acid-Fast Bacilli Tests among Waste Workers in Gresik, Indonesia - Utomo, Budi; Fatmaningrum, Widati; , Sulistiawati; Fauziyah, Shifa; Khuen, Chan Chow; Fadhilah, Nur; Sucipto, Teguh Hari (Folia Medica Indonesiana, 2024)
Highlights: 1. This study was the first in Gresik, Indonesia, to conduct mass screening of tuberculosis among waste workers, comprising various demographic profiles. 2. Although the tuberculosis screening of the waste workers showed negative results, mass examination using an acid-fast bacilli smear remains crucial to detect latent infections and prevent transmissions. Abstract Tuberculosis is a major source of illness and mortality worldwide. Therefore, tuberculosis screening is important to increase the number of active case-finding in a community. Bacteriological examinations can be used to initiate community-based active case-finding. Waste workers face a high risk of contracting Mycobacterium tuberculosis due to their constant exposure to waste. This study aimed to conduct bacteriological examinations to identify tuberculosis infections among waste workers in Gresik, Indonesia, who were considered a high-risk group. An analytical observational study was carried out throughout September 2023 in the Ngipik subdistrict, Gresik, East Java, Indonesia. The primary study was conducted using a cross-sectional design using interviews, measurements, and sputum examinations for all samples. The screening involved a total of 72 waste workers who had daily contact with various types of sewage and waste, including medical waste. The data were analyzed descriptively because of the constant variable. Following the analysis, the data were presented using a table and a figure. According to the acid-fast bacilli examinations, all of the samples yielded negative results. Nevertheless, this study concludes that it is imperative to carry out mass tuberculosis screening in various settings, specifically among those with a high risk. Mass screening can uncover the potential of latent tuberculosis and, thus, reduce its transmission.